Sustainable Development of Fisheries and Aquaculture in North Africa: Current Status and Future Prospects - Paruğ, Şenol; Jabbr, Abdulhamid; Lazrag, Fathia A. H. (Kastamonu University, 2024)
This paper delves into the fisheries and aquaculture sectors of five North African countries—Morocco, Algeria, Tunisia, Libya, and Egypt—highlighting their critical roles in economic stability and food security amid increasing regional demands for animal protein. Despite the rich marine ecosystems and substantial contributions to national economies and employment, most of these regions face several challenges in fisheries management due to limited knowledge, weak institutional frameworks, and insufficient international cooperation. The paper emphasizes the necessity of transitioning towards sustainable aquaculture practices to preserve natural fish stocks and augment food production capacities. Although legal and sustainable capture fisheries remain vital, the focal point of this review is the potential for aquaculture to meet the growing population's needs without exacerbating the pressures on marine ecosystems. The paper evaluates the current state of fisheries management, identifies challenges in scaling aquaculture, and discusses innovative practices that could lead to more sustainable and productive outcomes. The study calls for improved management strategies, enhanced research and training, and more significant investment in aquaculture to ensure sustainable development of the fisheries sector, ultimately contributing to food security, economic growth, and conservation of marine biodiversity.
Keywords: Kuzey Afrika balıkçılığı; Aquakültür gelişimi; Balıkçılık yönetimi; Sürdürülebilir uygulamalar; Koruma stratejileri; Balıkçılığın ekonomik etkisi; North African Fisheries; Aquaculture development; Fisheries management; Sustainable practices; Conservation strategies; Economic impact of fisheries; Balık Yetiştiriciliği; Sucul Kültür ve Balıkçılık (Diğer); Aquaculture and Fisheries Stock Assessment; Aquaculture and Fisheries (Other); Sucul Kültür ve Balıkçılık Stok Değerlendirmesi; Pisciculture; 2. Zero hunger; 1. No poverty; 15. Life on land; 12. Responsible consumption; 13. Climate action; 11. Sustainability; 8. Economic growth; 14. Life underwater